2016
DOI: 10.1007/s00281-016-0602-0
|View full text |Cite
|
Sign up to set email alerts
|

The origin of DCs and capacity for immunologic tolerance in central and peripheral tissues

Abstract: Dendritic cells (DCs) are specialized immune sentinels that play key role in maintaining immune homeostasis by efficiently regulating the delicate balance between protective immunity and tolerance to self. Although DCs respond to maturation signals present in the surrounding milieu multiple layers of suppression also co-exist that reduce the infringement of tolerance against self-antigens. These tolerance inducing properties of DCs are governed by their origin and a range of other factors including distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 194 publications
(242 reference statements)
0
61
0
Order By: Relevance
“…Recent literature has shown that the presence of increased lymphocytic infiltrates in MM alone may not be as significant as the functional activity of these cells in combating MM . Thus, we queried immune cell–specific gene transcript signatures, which revealed progressive increases in exhausted T cells, regulatory T cells (Tregs) and tolerogenic dendritic cells (DCs) gene signatures (Figure A‐C). RT‐PCR confirmed progressive increases in Treg activity (TGF‐β and IL‐10) and immunoregulatory markers (CTLA‐4, PD‐L1, PD‐L2 and IDO1) associated with exhausted T cells (Figure D‐I).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature has shown that the presence of increased lymphocytic infiltrates in MM alone may not be as significant as the functional activity of these cells in combating MM . Thus, we queried immune cell–specific gene transcript signatures, which revealed progressive increases in exhausted T cells, regulatory T cells (Tregs) and tolerogenic dendritic cells (DCs) gene signatures (Figure A‐C). RT‐PCR confirmed progressive increases in Treg activity (TGF‐β and IL‐10) and immunoregulatory markers (CTLA‐4, PD‐L1, PD‐L2 and IDO1) associated with exhausted T cells (Figure D‐I).…”
Section: Resultsmentioning
confidence: 99%
“…SOCS3 expression by dendritic cells has not previously been described in human melanoma. Increased cytokine IL‐10 in the immune microenvironment has been reported to increase SOCS3 expression and IL‐10 secretion by DCs, which prolong Treg cell function . Treg cells, in turn, contribute to T‐cell exhaustion, which mount ineffective immune responses against cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accumulating body of evidence demonstrates that different DC subsets are responsible for specialized immune functions. DCs imprint naïve responses to direct the differentiation of CD4 helper T cells into T H 1, T H 2, T H 17, Tfh, Tr1, and Treg (914). Multiple specialized subtypes of DCs that have been identified can be distinguished by surface markers, which have recently been correlated to their unique transcriptome based programs across mice and humans (1521).…”
Section: Introductionmentioning
confidence: 99%
“…Devi and Anandasabapathy review the development of tolerogenic DCs in different tissues and provide and exhaustive evaluation of the transcriptional programs that control them (4). Finally, one of the best-characterized tolerogenic functions of DCs is the promotion of Treg differentiation.…”
mentioning
confidence: 99%